(untitled) (Studia Prawnicze / The Legal Studies, 2023)
Zobowiązania umowne w prawie prywatnym międzynarodowym zostały obszernie przedstawione w literaturze w przeciwieństwie do zobowiązań nie wynikających z czynności prawnych. Autor w niniejszej pracy omawia przebieg prac kodyfikacyjnych regulujących zobowiązania nie wynikające z czynności prawnych. Opisuje osiągniecia polskiej doktryny przedwojennej przy opracowaniu polskiego prawa międzynarodowego prywatnego z 1926 r., ukazując m. in. spór pomiędzy Zollem a Allerhandem, który miał miejsce w trakcie prac kodyfikacyjnych. Ponadto przytacza także orzecznictwo w tej materii przed wybuchem II wojny światowej. Autor przedstawia wpływ osiągnięć polskiej przedwojennej doktryny na prace kodyfikacyjne powojennej Polski i na obecny kształt regulacji. Contractual obligations in private international law have been extensively presented in the literature in contrast to non-contractual obligations. In this paper, the author discusses the course of the codification work regulating obligations that do not arise from legal transactions. He describes the achievements of Polish pre-war doctrine in the drafting of the 1926 Polish Private International Law, revealing, among other things, the dispute between Zolle and Allerhand that took place during the codification work. In addition, he also cites case law on the subject prior to the outbreak of the Second World War. The author presents the influence of the achievements of Polish pre-war doctrine on the codification work of post-war Poland and on the current shape of the regulation.